A novel privacy preserving blockchain based secure storage framework for electronic health records. Issue 3 (3rd April 2022) - Kumar, Anil; Kumar, Ravinder; Sodhi, Sartaj Singh
Abstract: Despite the continuous improvement of healthcare technology, implementing a patient health record system still has a significant challenge due to its sensitivity. Apart from storing and sharing patient data across various healthcare facilities, the system also has a tendency to distribute the data among various providers. Most patient health record systems (EHRs) use a centralized management structure to store and transmit patient information. This approach can create privacy concerns as it transfers sensitive information to a healthcare facility. Digitized Electronic Health Record EHRs that stores the patient's medical history gathers from various IoT devices or from the centralized or decentralized database. These database records are often shared among various healthcare organizations. Most patient health record systems typically adopt a centralized approach and store their patient information in the cloud. This approach can raise privacy concerns due to the amount of sensitive information that is stored in the cloud. This paper proposes blockchain framework for secured electronic health records sharing and provides full data access to the patient, who is the owner of his health records. With this novel approach, our framework applies the Ethereum blockchain smart contracts, the Inter-Planetary File System (IPFS) as an off-chain storage system and key management. Blockchain based encryption creates an effective approach while sharing health records in distributed framework. Proposed framework is more secure than previously available framework. EHR's will not be accessible from unauthorized users.